THE INFLUENCE OF BRAND EQUITY, STORE ATTRIBUTES AND MARKETING DIRECTORS ON PURCHASING DECISIONS - Baitullah, Muhammad Iqbal; Darojat, Ilma; Rosyid, Muhammad Abdul (Universitas Muhammadiyah Tangerang, 2024)
The purpose of this study was to determine the effect of Brand Equity, Store Attributes and Direct Marketing on Purchasing Decisions at Indomaret Hasyim Ashari Banjar. The research method used is descriptive and associative method. The population in this study amounted to 96 customers. The sampling technique used purposive sampling method, namely the technique of determining the sample with certain considerations, using the Lemeshow formula. The results showed that the t-count value was 2.615 with a t-table value of 1.98552 which meant that there was a positive and significant influence between brand equity (X1) on purchasing decisions (Y), the t-count value was 3.840 with a t-table value of 1.98552 which means that there is a positive and significant influence between store attributes (X2) on purchasing decisions (Y). Y) and this calculated F value of 33.434 > F table of 2.70 it can be concluded that brand equity (X1), store attributes (X2) and direct marketing (X3) have a significant effect on purchasing decisions (Y).